(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Background: Although the corona virus disease 2019 (COVID‐19) outbreak is a global public health challenge, clinical patterns of children with COVID‐19 still remain unclear as most studies on COVID- 19 have focused on adults and only a small number of studies included pediatric patients. Objective: This study was done to observe the demographic profile, clinical presentation, laboratory finding and outcome of hospital-admitted children diagnosed as COVID-19. Method: This was a observational study done in Department of Paediatrics at Holy Family Red Crescent Medical College Hospital, Dhaka, Bangladesh from October 2021 to March 2022 for duration of six month. This study included all admitted children from newborn up to 14 years of age diagnosed with COVID-19 either by RT-PCR or by HRCT scan of the chest. Results: Among 35 patients mean age was 48.64 ± 63.10 month and 62.8% were male and 37.1% were female. Most common presentations were fever and cough both were (77.1%) followed by diarrhoea and vomiting which were 37.1% and 28.5% respectively. Leucopenia was noted in 22.8% patients. Chest X-Ray abnormalities were found in 60% of patients, bilateral patchy shadows were most common (24.2%) followed by consolidation (17.1%). 1 patient needed PICU, rest of the 34 (97%) patient in this study were discharged after full recovery. Conclusion: Clinical feature of COVID-19 in children differs from adult cases. Although fever and cough are main clinical symptoms, diarrhoea and vomiting are also common presenting symptoms in this study. Biochemical parameters like serum ferritin, D-dimer were also unremarkable and outcome was generally favourable. Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S14-S19